2018
DOI: 10.4103/meajo.meajo_3_17
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral congenital nasolacrimal duct obstruction, is it an amblyogenic factor?

Abstract: BACKGROUND/AIMS:To evaluate the refractive status, axial length, and prevalence of amblyopia among Saudi children with unilateral congenital nasolacrimal duct obstruction (UCNLDO) compared to the unaffected fellow eye.METHODS:A retrospective chart review was performed for children with UCNLDO at two eye institutes in Eastern Saudi Arabia from 2009 to 2015. The outcomes of syringing determined UNCLDO. The risk factors for amblyopia were defined as anisometropia of (spherical equivalent) >1.5 D, hyperopia >3.5 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…Additionally, children between the ages of 1 and 10 years demonstrated a heightened incidence of the condition. The incidence of congenital nasolacrimal duct obstruction (CNLDO) in neonates is approximately 5%, with over 90% of affected children experiencing spontaneous resolution without specific treatment within one year [ 16 ]. In cases of severe CNLDO, lacrimal passage irrigation or topical antibiotics may be utilized, although there is no consensus on the optimal timing for intervention [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, children between the ages of 1 and 10 years demonstrated a heightened incidence of the condition. The incidence of congenital nasolacrimal duct obstruction (CNLDO) in neonates is approximately 5%, with over 90% of affected children experiencing spontaneous resolution without specific treatment within one year [ 16 ]. In cases of severe CNLDO, lacrimal passage irrigation or topical antibiotics may be utilized, although there is no consensus on the optimal timing for intervention [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wrodzona niedrożność dróg łzowych może być kolejną przyczyną zaburzeń widzenia, nie zawsze dostrzeganą w porę, która dotyczy 5-20% dzieci [7,8]. Nieleczona powoduje zalega-nie łez i często wydzieliny śluzowej i/lub ropnej na powierzchni rogówki lub gałki ocznej, co może zaburzać prawidłowy rozwój gałki ocznej, a także sprzyjać powstaniu niedowidzenia i wady refrakcji [7,8].…”
Section: Mirosława Grałek Anna Niwaldunclassified
“…Wrodzona niedrożność dróg łzowych może być kolejną przyczyną zaburzeń widzenia, nie zawsze dostrzeganą w porę, która dotyczy 5-20% dzieci [7,8]. Nieleczona powoduje zalega-nie łez i często wydzieliny śluzowej i/lub ropnej na powierzchni rogówki lub gałki ocznej, co może zaburzać prawidłowy rozwój gałki ocznej, a także sprzyjać powstaniu niedowidzenia i wady refrakcji [7,8]. W pierwszych tygodniach życia, w okresie krytycznego rozwoju widzenia, nadmierny menisk i film łzowy oraz wydzielina zapalna leżąca na rogówce zmieniają moc optyczną przedniej powierzchni gałki ocznej, mogącą skutkować powstaniem wady refrakcji i różnowzroczności z wtórnym niedowidzeniem.…”
Section: Mirosława Grałek Anna Niwaldunclassified
“…Also, when pressure is applied over the lacrimal sac, a reflux of mucoid or mucopurulent material from the punctum is observed. Sometimes, the residual debris undergoes a bacterial infection leading to purulent conjunctivitis [3,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have confirmed an increased risk for anisometropia and amblyopia in patients with CNLDO (especially long-term untreated obstructions) [22][23][24][25]. However, the effect of long-term epiphora on visual development in children is debatable and some studies reported no significant differences between children with CNLDO and general population [17,26,27].…”
Section: Introductionmentioning
confidence: 99%